2021
DOI: 10.1177/0272989x20984134
|View full text |Cite
|
Sign up to set email alerts
|

User Involvement in the Design and Development of Patient Decision Aids and Other Personal Health Tools: A Systematic Review

Abstract: Background When designing and developing patient decision aids, guidelines recommend involving patients and stakeholders. There are myriad ways to do this. We aimed to describe how such involvement occurs by synthesizing reports of patient decision aid design and development within a user-centered design framework and to provide context by synthesizing reports of user-centered design applied to other personal health tools. Methods We included articles describing at least one development step of 1) a patient de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 31 publications
1
68
0
Order By: Relevance
“…This included consultation with 15 external experts and four rounds of pilot data extraction and refinement of response processes across randomly selected sets of five articles each time (total: 20 articles). We had also confirmed the accuracy of the extracted data with the authors of the original articles included in the systematic review and found very low rates of error [13].…”
Section: Response Processmentioning
confidence: 56%
See 4 more Smart Citations
“…This included consultation with 15 external experts and four rounds of pilot data extraction and refinement of response processes across randomly selected sets of five articles each time (total: 20 articles). We had also confirmed the accuracy of the extracted data with the authors of the original articles included in the systematic review and found very low rates of error [13].…”
Section: Response Processmentioning
confidence: 56%
“…Content validity (point 1 in the validity framework [31]) refers to how well items match the definition of a construct. To ensure content validity of items, in our original systematic review, we had used foundational literature [15,16,18,[43][44][45]; held monthly or bimonthly consultations in person and by teleconference over the course of 2 years within our interdisciplinary group of experts, including patients, caregivers, health professionals, academic researchers, and other stakeholders; and consulted with 15 additional experts outside the research team [13]. Discussions over the years of the project centered on the items themselves as well as prioritization of items according to their relevance within our conceptual framework.…”
Section: Content Validitymentioning
confidence: 99%
See 3 more Smart Citations